IMPACT ANALYSIS OF CAPITAL ADEQUACY RATIO (CAR) AND RETURN ON ASSET (ROA) ON FINANCING OF MURABAHA ON SHARIA BANK IN INDONESIA PERIOD YEAR 2014-2018 - Afiyanti, Arsita; Hardiyanti, Widhian (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
This Research aims to discuss and analyze the capital adequacy ratio (CAR) and the asset ratio (ROA) to Murabaha financing. The data population listed are Islamic commercial banks registered at Bank Indonesia for the period 2014-2018 using purposive sampling techniques obtained 60 data samples. The analytical tool used is multiple linear regression analysis.The results of this study explain that CAR is positive towards Murabaha financing. Whereas ROA has a significant negative impact on Murabaha financing.Â Keywords: Capital Adequacy Ratio (CAR), On Asset Ratio (ROA), Murabaha Financing